POPULATION DENSITY AND DISTRIBUTION PATTERNS OF KALAMBODO MUSSEL (Anodonta woodiana) IN THE SUB WATERSHED OF LAHOMBUTI RIVER, LAHOTUTU VILLAGE, KONAWE DISTRICT SOUTH EAST SULAWESI - Muhammad Fajar Purnama; Abdullah Abdullah; Alfi Kusuma Admaja; La Ode Alirman Afu (AQUASAINS, 2019)
Abstrak The research was conducted in November 2018 - February 2019 in the Sub-watershed of the Lahombuti River in Lahotutu Village, Konawe Regency. The purpose of this study was to determine aspects of population density and distribution patterns of the Kalambodo (A. woodiana) in the Sub watershed of the Lahombuti tributary in Lahotutu Village, Wonggeduku District, Konawe Regency. The sampling location was determined using the purposive random sampling method. Sampling of Kalambodo (A. woodiana) was carried out at the location with the greatest abundance of A. woodiana, in the Sub watershed of the Lahombuti tributary of Lahotutu Village, on the "Main Rice Field Irrigation Channel" (diameter: ± 1,75 m, length: ± 4500 m, depth: ± 110 cm). Sampling of A. Woodiana was carried out at the same station with different spot sampling points. The Kalambodo samples were taken using a 1x1 m2 sized transect on 3 randomly assigned plots. The range of A. woodiana density per sub station is November 2018 amounting to 67-95 ind/m2, December 2018 is 41-61 ind/m2, January 2019 is 41-148 ind/m2 and February 2019 is 101- 114 ind/m2. The average density based on the period from the highest to the lowest is obtained in February 2019, January 2019, November 2018, and December 2018, which is 106.67 ind/m2, 81.33 ind/m2, 78 ind/m2, and 53 ind/m2, respectively. The distribution pattern of A. woodiana in the Sub-watershed of the Lahombuti River Basin generally shows a uniform category (Id <1), with a range of morisitha index values of 0.65-0.87.